Chemical and physical modifications of electrospun keratin nanofibers induced by heating treatments. Issue 15 (20th February 2014) - Varesano, Alessio; Vineis, Claudia; Tonetti, Cinzia; Ramírez, Diego Omar Sánchez; Mazzuchetti, Giorgio
ABSTRACT In this study, we aimed to examine to study the effects of heating treatments on wool‐derived keratin nanofibers obtained by electrospinning. Interestingly, the keratin nanofibers did not lose their nanofibrous shape at high temperatures. On the contrary, the diameter of keratin nanofibers significantly decreased after heating. Even the chemical structure of the keratin was not significantly altered by heating, as observed by IR spectroscopy, except for a shoulder at 1720 cm−1 and the amide III band. The spectral feature changes matched the formation of crosslinking amide bonds between protein chains well. Moreover, for various applications, it is essential that nanofibers are stable in water. Heating treatments were carried out at different temperatures and times to assess what heating conditions gave the keratin nanofibers water stability. Finally, no significant changes in the thermal behavior were observed in the samples after heating treatments compared to the untreated keratin nanofibers; this was a sign of negligible or slight degradations of the protein chains. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40532.